(untitled) (Bangladesh Veterinarian, 2013)
The keeping quality of raw cow milk at room temperatures was evaluated in different containers with or without sodium bicarbonate. Milk samples stored in containers of glass, tinned iron, plastic, aluminium, earthen and bronze at 12 to 20oC were analyzed every two hours for acidity and clot-on-boiling (COB) tests. Milk from the organised dairy farm kept well in aluminium containers up to ten hours, but milk from villages deteriorated after six hours. The keeping qualities of milk were poorer in other containers, and worst in earthen container. In COB test, milk from BAU dairy farm showed no changes for eight hours in all containers. Milk in aluminium container kept 14 hours, but only eight hours in earthen pot. Milk collected from villages kept for ten hours in aluminium container and six hours in earthen container. After mixing sodium bicarbonate 0.05 and 0.1%, milk kept well up to 16 hours, and up to 20 hours with 0.15% based on acidity test. Addition of Na2Co3 improved the keeping quality till 24 hours of storage at 10 19oC in aluminium container. DOI: http://dx.doi.org/10.3329/bvet.v29i2.14348 Bangl. vet. 2012. Vol. 29, No. 2, 90-95